DIGITAL TRANSFORMATION IN UKRAINE DURING WAR AND ITS ASPECTS OF INNOVATION IN THE FIELD OF ENTERPRISE MANAGEMENT - MAMONTENKO, Nataliya (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The initial presentation of analog documents of all types in digital format, referred to as digitization, was only the initial stage for digitization. The active use of digital technologies in all spheres has led to the growing dependence of society on digital data. As a result, it is necessary to talk about the need for purposeful transformation of the economy into a digital one. Despite all the complexity of the situation in which Ukraine found itself as a result of the full-scale invasion of the Russian Federation, measures are being taken and events are taking place aimed at the transition to a digital economy. First of all, these changes take place at the macro level, changing the general environment of enterprises. The prerequisites for such changes are the presence of normative documents that establish Ukraine's desire to transform the economy into a digital one. In August 2024, the government adopted priority directions and tasks (projects) of digital transformation for 2024–2026, which takes into account the current situation in Ukraine and is also aimed at harmonizing Ukrainian and European legislation in the field of informatization Another important one is the signing of the Framework Convention of the Council of Europe on Artificial Intelligence, which will allow Ukrainian enterprises to fully utilize the opportunities associated with the use of AI. In addition, infrastructural prerequisites were created for the formation or improvement of various registers, which in turn will allow to speed up the automatic processing of information by enterprises to meet their economic needs. With the support of international partners, the activities of individual enterprises that are primarily engaged in the development of digital defense technologies are financed. However, there is an urgent need for the adoption of normative documents that create the prerequisites for the digitalization of the economic activities of industrial enterprises, including the creation of prerequisites for import substitution in the production of important products of defense importance. However, Ukraine's capabilities in the field of digitization depend significantly on the course and duration of the war.
Keywords: digitalization; digital transformation; military economy; enterprise management; innovativeness